PENGARUH KOMPETENSI, INDEPENDENSI DAN GENDER TERHADAP KUALITAS AUDIT (STUDI PADA INSPEKTORAT SE - PULAU LOMBOK) - SUKRIATI, SUKRIATI; Basuki, Prayitno; Surasni, Ni Ketut (Universitas Sam Ratulangi, 2020)
The study examines the influence of competence, independence and gender to audit quality of internal auditors. The respondent in this study where who worked for the inspectorate of Lombok. The number auditor who observed in this study was 136 auditors. They come from some auditors who worked in the inspectorate of Lombok. The method of determining the sample was purposive sampling method, the data processing methods. That used cy researcher were the multiple regression analysis.The result show that the competence independence significantly to audit quality of internal auditors but gender no significantly to audit qualityÂ Keyword:Â competence, independence, gender audit quality